Development of middle-range theories in nursing - Tânia Alteniza Leandro; Marília Mendes Nunes; Iane Ximenes Teixeira; Marcos Venícios de Oliveira Lopes; Thelma Leite de Araújo; Francisca Elisângela Teixeira Lima; Viviane Martins da Silva
ABSTRACT Objective: To identify in the literature how Middle-Range Theories (MRT) are being developed in Nursing. Method: Integrative review on the databases Lilacs (Latin American and Caribbean Literature in Health Sciences), Scopus, Cinahl (Cumulative Index to Nursing and Allied Health Literature), Web of Science and PubMed portal, using the keywords middle range theory and nursing, as well its Portuguese correspondents (Lilacs), and the Boolean operator AND. The sample included 25 articles. Results: All articles presented concepts related to MRT. Most developed a synthesis picture. Some theories have formulated specific propositions, hypotheses, and names. Only 16 articles cited the methodological framework, while 22 used theories or models for theoretical foundation and 11 carried out literature reviews. Final considerations: The development of MRT included the presentation of fundamental concepts, synthesis, propositions, hypotheses and specific name. The MRT is recognized as a way of developing knowledge to guide the nursing practice.